Obligatory third party liability insurance for professionals - Bożek, Diana Renata (Copernican Journal of Finance & Accounting, 2013)
For several years obligatory third party liability insurance are getting more and more popular in Poland. Polish legislator obliged many professional groups to have such insurance. Author want to answer the question: if this situation is a necessity or an example of incorrect legislator’s activity? This article presents short history of third party liability insurance, philosophical basis of the regulation and shifts in the conception of civil liability caused by insurance. Author refers also to an influence which deregulation of access to regulated professions exert on obligatory third party liability insurance.